Examining the Impact of Attentional Control and Ethnic Identity on Racial Shooting Bias - Durriseau, Jaymes (Advances in Social Sciences Research Journal, 2025)
The current study examined how cognitive factors (attentional control) and social factors (ethnic identity) played a role in shooting decisions in the first person shooter task (FPST). This examination was performed with an understudied population within the FPST literature, Black American college students. Replicating the typical findings of the FPST that used mostly White Americans, the current study also found racial shooting bias against Black targets when compared to their White counterparts. Attentional control, as measured through the Antisaccade task, showed no influence on shooting decisions. Ethnic Identity, measured with the Multigroup Ethnic Identity Measure (MEIM), had an impact on shooting decisions. Black American participants with low ethnic identity scores showed racially biased shooting decisions against Black targets. This biased shooting behavior was not found for Black American participants with high ethnic identity.